Los felinos silvestres del departamento de Caldas, en la región andina de Colombia: composición, distribución y conservación - Escobar-Lasso, Sergio; Cerón-Cardona, Juliana; Castaño-Salazar, John Harold; Mendieta-Giraldo, Leonardo; Ospina-Herrera, Oscar (THERYA, 2014)
Introduction: The department of Caldas is located in the Central Andes of Colombia, it includes a mosaic of environments that originally was conformed by páramos, sub-Andean and Andean forests, and rainforests. Although several studies have contributed to the knowledge of wild felids that inhabit the department of Caldas, Central Andes of Colombia, to date, there are no a publications summarizing the existing information on the felids in this area. The aim of this paper is to review the composition, distribution and conservation status of felids of the Caldas department. Materials and methods: To carry out the review of the composition, distribution and conservation status of the wild cats of Caldas department, were taken into account: A) Specimens, or part of these, deposited within biological collections. B) Records in scientific literature. C) Photographic records. D) Records of live individuals coming from the Caldas department who entered to the Center of Care, Assessment and Rehabilitation of Wildlife of the Regional Autonomous Corporation of Caldas (Corpocaldas). E) Records coming from attacks by wild cats on sheep, cattle and horses within the department. Results and discussion: We identified 33 locations with records of wild felids, which belong to six species: Leopardus pardalis (Ocelote), L. wiedii (Margay), L. tigrinus (Oncilla), Puma yagouaroundi (Jaguarundí), P. concolor (Puma), and Panthera onca (Jaguar). In this work, we identified two areas of the department where most of the records were made. The first area is located in the south-central portion of Caldas and it includes the majority of the records of L. tigrinus and P. concolor. The second area is located in the northeastern portion of the department and it is associated with all of the records of L. wiedii and most of the records of L. pardalis and P. yagouaroundi. The main threats to the survival of wild cats in Caldas are: habitat loss, fragmentation, hunting, as well as road mortality. Since 1999, there are no records of Panthera onca for Caldas, and more research is required to confirm whether this species still inhabits the department.